PENGARUH ELECTRONIC WORD OF MOUTH (EWOM) TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK BIBIR BARENBLISS DI BANDAR LAMPUNG - Annisa Rizki Indriani; Dorothy RH Pandjaitan (Yayasan Nusantara Hasana Berdikari, 2025)
Advances in information technology have driven shifts in consumer behavior when making purchasing decisions, particularly through the phenomenon of Electronic Word of Mouth (EWOM) on social media and e-commerce platforms. This study aims to investigate the influence of the three main dimensions of Electronic Word of Mouth (EWOM) intensity, Valence of Opinion, and content on purchasing decisions for Barenbliss lip cosmetics in Bandar Lampung. The research method employed is a quantitative approach using descriptive and confirmatory techniques. Data was collected through a questionnaire distributed to consumers who have used Barenbliss lip cosmetics and been exposed to digital reviews of the product. Analysis was conducted using SPSS version 25.0. The results of the study indicate that all independent variables in this study intensity, Valence of Opinion, and content have a positive and significant effect on purchasing decisions, both partially and simultaneously. This is evidenced by the significance values of each hypothesis test, all of which are below 0.05, thus accepting the proposed hypotheses. Intensity indicates that the more frequently someone is exposed to reviews, the greater the likelihood of making a purchase. Positive opinion valence enhances consumer confidence, and informative and high-quality content strengthens purchasing decisions.